Vaginal Colonization by Escherichia coli in Pregnant Women at King Abdulaziz University Hospital, Jeddah, Saudi Arabia - Taghreed J. Jamal; Hassan El-Banna A. Younus; Hassan S. Abduljabbar; Asif A. Jiman-Fatani; Amal F. Makled (Journal of King Abdulaziz University: Medical Sciences, 2023)
Maternal and neonatal infections by Escherichia coli remain a challenging problem for obstetricians and pediatricians. This study aims to determine the prevalence of vaginal colonization by Escherichia coli among pregnant women attending the Antenatal Clinics at King Abdulaziz University Hospital in Jeddah- Saudi Arabia, and to investigate the susceptibility of isolated Escherichia coli to the most commonly used antimicrobials. In this study, 100 pregnant women in the last trimester and 25 non-pregnant women were screened for vaginal colonization of Escherichia coli. The suspected colonies were identified by conventional methods and were confirmed by automated technology "Vitek 2 System". Also, antimicrobial susceptibility tests were done by the same methods". Escherichia coli isolates were serotyped to detect the presence of K1 antigen. Out of 100 pregnant women in the last trimester; twenty-one (21%) were Escherichia coli positive. Also, out of 25 non-pregnant women; four (16%) were Escherichia coli-positive. All of the isolated Escherichia coli were susceptible to most antimicrobial agents. The percentage of vaginal Escherichia coli resistance to trimethoprim/sulfamethoxazole, ampicillin and piperacillin ranged from 38.1% to 42.9%. The virulence factor K1 antigen was demonstrated in 42.9% of Escherichia coli -positive pregnant women.